Studi Eksperimental Pengaruh Variasi Bahan Kering Terhadap Produksi dan Nilai Kalor Biogas Kotoran Sapi - Wiratmana, I Putu Awing; Sukadana, I Gusti Ketut; Tenaya, I Gusti Ngurah Putu (Jurnal Energi Dan Manufaktur, 2013)
Biogas produced from the fermentation of organic matter by anaerobic bacteria. The calorific value contained in biogas depends on the concentration of CH4. Tthe production of CH4 in biogas is affected by CN ratio on dry matter which is between 25:1 - 30:1. Cow manure has a C-N ratio of 18:1, so it should be added to other materials, namely rice husk which has a C-N ratio of 65:1. The purpose of this study is to investigate the effect of the addition of rice husk to the production and calorific value of manure biogas.The test was performed with a batch system with the addition of15%, 18%, 21% and 24% of the total rice husk 100% by weight of dry ingredients used. Observed data was a water manometer height change (?h), the mass of biogas and gas composition on biogas.The results shows that the addition of 21% rice husk 100% had the highest production of 0.0597 kg and the highest calorific value is 55,017 kJ and 75.034 kJ by eksperimental and theoretical with CH4 compositon was found 80%.
Keywords: C-N ratio, biogas production, experimental calorific value, theoretical calorific value